2011
DOI: 10.4061/2011/818672
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Pathogenesis and Clinical Implications of Hepatocellular Carcinoma

Abstract: The prognosis of hepatocellular carcinoma (HCC) is affected by tumoral factors and liver functions; therefore it is often difficult to select the appropriate therapeutic methods for HCC. Recently, two global phase III trials showed that sorafenib, which is a tyrosine kinase inhibitor, improved the prognosis of patients with advanced HCC. As a new therapeutic strategy for HCC, sorafenib is expected to expand the indication for HCC in the future. However, it alone is insufficient for the molecular-targeted treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) ranks in prevalence and mortality among the top 10 cancers all over the world. The estimated number of new cases of HCC had risen to 564, 300 and 548, 600 patients with HCC had died, representing 97.2% of persons with this diagnosis [2]. The development and progression of HCC in humans is a multi-step, long-term process, characterized by the progressive accumulation of genetic and epigenetic alterations associated with sequential evolution of morphologically distinct stages culminating in the formation of fully developed HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) ranks in prevalence and mortality among the top 10 cancers all over the world. The estimated number of new cases of HCC had risen to 564, 300 and 548, 600 patients with HCC had died, representing 97.2% of persons with this diagnosis [2]. The development and progression of HCC in humans is a multi-step, long-term process, characterized by the progressive accumulation of genetic and epigenetic alterations associated with sequential evolution of morphologically distinct stages culminating in the formation of fully developed HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HCC accounts for between 85 and 90% of all cases of primary liver cancer and is the third leading cause of mortality from cancer worldwide and the fifth most common type of malignancy (1)(2)(3)(4). It has been reported that ~21,000 cases of HCC are diagnosed and ~700,000 patients succumb to the disease worldwide annually (5).…”
Section: Introductionmentioning
confidence: 99%
“…3 The stem cell theory of cancer was first established in hematopoietic malignancies and recently extended to solid tumors including HCC. In this hierarchical model, self-renewing CSCs are at the apex and ultimately give rise to all other tumor cells.…”
Section: Commentmentioning
confidence: 99%